A Dynamic Market Mechanism for Combined Heat and Power Microgrid Energy Management. Issue 1 (July 2017) - R Nudell, Thomas; Brignone, Massimo; Robba, Michela; Bonfiglio, Andrea; Delfino, Federico; Annaswamy, Anuradha
Abstract: This paper develops a dynamic market mechanism (DMM) to optimally allocate electric and thermal power in a combined heat and power microgrid. The market is formulated as a receding horizon constrained optimization problem, from which an optimal automated transactive procedure is developed. The market operation is distributed in nature and incorporates the most up-to-date electric and thermal load estimates and renewable generation. These properties make our microgrid DMM, µDMM, attractive for microgrid energy management systems, as new smart buildings, battery storage systems, and renewable energy resources can be added in a plug-and-play fashion without reformulating the optimization problem and without adding computational complexity to the EMS. The result of the market clearing is the spot prices and set-points for electric and thermal power in addition to non-binding estimates of future prices and set-points. The the market mechanism is simulated on a CHP Microgrid model based on the Smart Polygeneration Microgrid (SPM) located on the University of Genoa's Savona campus.